Facts about Wildlife Diseases: Capture Myopathy in Farmed White-Tailed Deer - Juan Manuel Campos Krauer (EDIS)
This publication discusses causes, clinical signs, and ways to reduce risk of capture myopathy in farmed white-tailed deer. Written by Juan M. Campos Krauer, and published by the Veterinary Medicine—Department of Large Animal Clinical Sciences, UF/IFAS Extension, January 2024.